Empowering consumers with aesthetic appeal and product involvement through co-design for value enhancement - E Thenral,; Suganthi, Dr.L. (The journal of contemporary issues in business and government, 2021)
Firms target customers who are interested to design their own product that is unique from a mass-produced product through co-design. This study aims to find whether the individual difference in visual appeal and product involvement influences the perceived value of co-design. Using convenience sampling survey method, 573 usable responses were collected and analyzed. The results indicate that product involvement partially mediates the relationship between the centrality of visual product aesthetic and perceived value of co-design. Hence, firms need to structure their co-design process for aesthetics and redefine the solution space such that it provides scope for aesthetic improvements. The firms can use social media to both identify and target customers with high product involvement and communicate value of co-designing the product through visually appealing marketing communications. Further, the co-design process should encourage customers to interact with the firm by providing adequate information about co- designing the product thus empowering them to actually design and develop unique products.